THE EFFECT OF NATURAL GUARD ADMINISTRATION IN DRINKING WATER ON ND-ANTIBODY TITERS IN BROILERS - Meidiana, Made Shanty; Ardana, Ida Bagus Komang; Dharmayudha, Anak Agung Gde Oka; Merdana, I Made; Sudimartini, Luh Made; Babikian, Yousef Haig Setrak; Babikian, Haig Yousef; Haliman, Rubiyanto Widodo; Yen, Theng In; Kristina; et al. (Buletin Veteriner Udayana, 2024)
The broiler is the largest sector producing protein sources in Indonesia. Poultry farms are susceptible to viral diseases, including the Newcastle Disease Virus (NDV). Viral diseases can be prevented by vaccination to increase antibody titters in broiler chickens. Induction of antibody titters can be increased by providing additional ingredients such as immune system stimulants known as immunomodulators. One material that can be used as an immunomodulator is the NATURALGUARD (NG). This research was conducted to determine the effect of NG supplementation in drinking water on ND antibody titters in broilers. This study used a completely randomized design with four treatments, namely P0 as a control without NG treatment, and P1, P2, and P3 were given NG treatment at doses of 1, 2, and 4 g/L, respectively adlibitum for 30 days starting at three days of age. Blood samples were taken on day one before treatment, 15 and 30 days after treatment for the hemagglutination inhibition (HI) test. The results showed that maternal antibodies against ND on the first day were protective but not uniform; the highest mean HI 4 log 2 titter was at P0 (512 ± 280.43) and the lowest at P2 (384 ± 140.21). The decrease in antibodies occurred at the age of 18 days to the highest at P0 and P3, namely 16 ± 0, and the highest at P2 (16.66 ± 4.13), and at the age of 33 days, the lowest titter was at P1 (4 ± 0) and the highest was at P2 and P3 (10±6.57). It can be concluded that NATURALGUARD supplementation shows an immunomodulating effect in broiler chickens that have not been re-vaccinated with Newcastle Disease through a slower regulation of decreasing antibody titters at NG supplementation doses of 2 and 4 g/L.